Implementation Assistance Driver System for Public Transportation Based on Embedded System - A Sumarudin; A Suheryadi; A Puspaningrum; E Prasetyo; Y N Azis (Sam Ratulangi University, 2020)
According to data from the World Health Organization (WHO) per year around 1.35 million people die as a result of traffic accidents. Therefore, one solution is the development of Smart Transportation, namely the implementation of the Advanced Driver Assistant System (ADAS) on public transportation. The purpose of this study is to provide a level of safety in public transportation in the form of providing recommendations in driving. ADAS is implanted in an Odroid device and then installed on public transportation. The system can provide speed recommendations, predict vehicle conditions whether safe or dangerous, and detect traffic signs. In its implementation the system provides speed recommendations using Artificial Intelligence (AI) which is the fuzzy logic method and to predict the condition of the vehicle using machine learning that is the Support Vector Machine method. The system output in the form of speed recommendations, vehicle safety predictions and traffic signs detection will be directly accepted by the driver both visually and soundly. From the test results, the system has an accuracy rate of 95.25% in predicting vehicle conditions.Keywords: Assistance driver system; artificial intelligent; embedded device; machine learning; odroidÂ Impelementasi Assistance Driver System untuk Transportasi Publik Berbasis Sistem EmbeddedABSTRAKMenurut data dari organisasi kesehatan dunia (WHO) per tahun sekitar 1,35 juta orang meninggal akibat kecelakaan lalu lintas. Salah satu solusinya adalah pengembangan smart transport, yaitu penerapan advanced driver assistant system (ADAS) pada angkutan umum. Tujuan penelitian ini memberikan tingkat keselamatan pada transportasi publik berupa pemberian rekomendasi dalam berkendaraan. Â ADAS ditanamkan dalam perangkat odroid dan kemudian dipasang pada transportasi umum. Sistem ini dapat memberikan rekomendasi kecepatan, memprediksi kondisi kendaraan apakah aman atau berbahaya, dan mendeteksi rambu-rambu lalu lintas. Dalam implementasinya sistem memberikan rekomendasi kecepatan menggunakan artificial intelligence (AI) yang merupakan metode logika fuzzy dan untuk memprediksi kondisi kendaraan menggunakan pembelajaran mesin yaitu metode support vector machine. Output sistem dalam bentuk rekomendasi kecepatan, prediksi keselamatan kendaraan dan deteksi rambu lalu lintas akan langsung diterima oleh pengemudi baik secara visual maupun suara. Dari hasil pengujian, sistem memiliki tingkat akurasi 95,25% dalam memprediksi kondisi kendaraan.Kata kunci: Assitance driver system; Â inteligensi buatan; perangkat tertanam; pembelajaran mesin; odroid